Cloud-Based Collaboration and SOLO Taxonomy in Deep Learning in Higher Education: Kolaborasi Berbasis Awan dan Taksonomi SOLO dalam Pembelajaran Mendalam di Perguruan Tinggi - Barokfi Mumtaz; Ayep Rosidi; Isnaini isnaini (Universitas Muhammadiyah Sidoarjo, 2025)
This study analyses the implementation of Google Docs in supporting deep learning among students using the SOLO Taxonomy in the Development of Evaluation Systems and PAI Learning Outcomes course. Twelve students participated in this qualitative case study. Data collection was conducted through observation, interviews, and documentation. The results of the study show that Google Docs enables real-time collaboration that facilitates student development from unistructural and multistructural levels to relational levels. However, the digital divide and unequal participation limit progress to higher extended abstract levels. This study confirms that digital collaborative tools aligned with the SOLO Taxonomy can support cognitive development when supported by appropriate infrastructure and teaching. To realise the full potential of deep and equitable learning, educational practices must prioritise digital learning policies, SOLO Taxonomy support, and a culture of sustainable collaboration. Highlights: Real-time document collaboration supported structured cognitive progression within group learning activities. Most students demonstrated integrated conceptual understanding at relational cognitive levels. Infrastructure limitations and uneven participation constrained higher-order knowledge generalisation. Keywords: SOLO Taxonomy, Deep Learning, Collaborative Learning, Cognitive Development, Islamic Education